A real-time web-based application of healthcare monitoring and notification system using IoT technology - Sinchai, Ananta; Thippakdee, Chanatip; Theeranukul, Chalesuan; Sri-Utaiwong, Chissanupong; Phasujit, Torkiat; Malithong, Pornpawee (My University, 2023)
Since the aging society has come, the number of elderly people seeking healthcare services from a hospital has increased. Most cases of senile patients including immobile patients are necessary to be admitted to the hospital, and are bedridden, but the quantity of beds is insufficient for them. With this reason, plenty of them is unavoidable to cure at home, known as home care. However, for home care, no nurse always takes care, and no suitable medical device is fully equipped to monitor like in the hospital. This is problematic because some patients might not show any seen physical symptoms and not get immediate help leading to serious conditions or even death. To provide instant help to the bedridden patients, a real-time web-based health multimedia monitoring and notification system utilizing IoT technology is proposed. The presented approach uses two vital sign indicators, oxygen saturation (SpO2) and pulse rate (PR) as criteria to notify both medical personnel and a caregiver. The experimental results have shown that the proposed system can create a notification alert at once through different media with the accuracy of 100%. By applying the proposed system, emergency care can be delivered to the bedridden patients in time.
Keywords: Bedridden patients; IoT; Multimedia monitoring system; Notification system; Pulse rate (PR); SpO2